2017
DOI: 10.1039/c7cp05276f
|View full text |Cite
|
Sign up to set email alerts
|

Complexation of β-cyclodextrin with dual molecular probes bearing fluorescent and paramagnetic moieties linked by short polyether chains

Abstract: Electron paramagnetic resonance (EPR) and fluorescence spectroscopies provide molecular-level insights on the interaction of paramagnetic and fluorescent species with the microenvironment. A series of dual molecular probes bearing fluorescent and paramagnetic moieties linked by flexible short polyether chains have been synthesized. These new molecular probes open the possibility to investigate various multi-component systems such as host-guest systems, polymeric micelles, gels and protein solutions by using EP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 51 publications
1
29
0
Order By: Relevance
“…Moreover, the changes in the fluorescence intensity are less for system F127‐3 that contains HPB in higher concentration. In a previous study on the behavior of Py(EG) n and Py(EG) n T probes, we have shown that complexation with cyclodextrin does not involve inclusion of the pyrene moiety into the cavity . In the presence of HPB, it is thus possible that the complexation involves the inclusion of ethylene glycol chains.…”
Section: Resultsmentioning
confidence: 89%
See 4 more Smart Citations
“…Moreover, the changes in the fluorescence intensity are less for system F127‐3 that contains HPB in higher concentration. In a previous study on the behavior of Py(EG) n and Py(EG) n T probes, we have shown that complexation with cyclodextrin does not involve inclusion of the pyrene moiety into the cavity . In the presence of HPB, it is thus possible that the complexation involves the inclusion of ethylene glycol chains.…”
Section: Resultsmentioning
confidence: 89%
“…Previously, the interaction with cyclodextrin of the molecular probes involved in this study was investigated by either fluorescence or EPR spectroscopy. We have found that both fluorescence and EPR parameters are sensitive to this interaction and we evidenced the role played by the linker in the geometry of the complex . The F127 systems investigated in this study were previously characterized macroscopically by dynamic rheometry and the tube inversion method (Figure S1, Supporting Information), in order to obtain the temperature corresponding to the transition from micelle to gel ( Table 1 ).…”
Section: Introductionmentioning
confidence: 73%
See 3 more Smart Citations